2016
DOI: 10.1039/c6lc00254d
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse polyethylene glycol diacrylate hydrogel microsphere formation by oxygen-controlled photopolymerization in a microfluidic device

Abstract: PEG-based hydrogels have become widely used as drug delivery and tissue scaffolding materials. Common among PEG hydrogel-forming polymers are photopolymerizable acrylates such as polyethylene glycol diacrylate (PEGDA). Microfluidics and microfabrication technologies have recently enabled the miniaturization of PEGDA structures, thus enabling many possible applications for nano- and micro- structured hydrogels. The presence of oxygen, however, dramatically inhibits the photopolymerization of PEGDA, which in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
105
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 62 publications
2
105
1
Order By: Relevance
“…Microfluidic platforms have been used to microfabricate hydrogel spheres with well-defined diameters, architectures, and chemical compositions [6064], as well as fibers of a particular architecture including hollow fibers and gradients within hydrogels [65]. Numerous studies have demonstrated the generation of cell-laden hydrogel microparticles using microfluidic devices[64].…”
Section: Spatial Control Of Hydrogelsmentioning
confidence: 99%
“…Microfluidic platforms have been used to microfabricate hydrogel spheres with well-defined diameters, architectures, and chemical compositions [6064], as well as fibers of a particular architecture including hollow fibers and gradients within hydrogels [65]. Numerous studies have demonstrated the generation of cell-laden hydrogel microparticles using microfluidic devices[64].…”
Section: Spatial Control Of Hydrogelsmentioning
confidence: 99%
“…It is an acrylate-based monomer and thus radical chain-growth polymerization was preferred as more suitable and common in photo-curable procedures. [19,20] Moreover, free radicals can be also added on the double bond of a graphene or CNT surface, enhancing the connectivity between carbon nanofiller and polymer matrix [21,22]. Fabbri et al have shown that PEGDA can be combined successfully with GO to form transparent and conductive coatings by photopolymerization [20].…”
Section: Introductionmentioning
confidence: 99%
“…The micro‐droplet can be regarded as an independent micro‐reactor and can be produced in a high‐throughput manner, rendering it an attractive tool for a variety of research fields . They include not only the biochemical applications such as a single‐cell analysis , an enzyme assay , and a PCR reaction but also the chemical synthesis for inorganic nanoparticles , organic nanoparticles , polymer microparticles , and colloidal microparticles . The micro‐droplet technology has demonstrated its ability to produce homogeneous ones with a predictable size in a modest fashion .…”
mentioning
confidence: 99%